Assessing the impacts of future urban expansion on multiple ecosystem services in the transnational area of Changbai Mountain - Chen, Ruikang; Zhang, Da; Nan, Ying; Feng, Hengdong; Geng, Xin (Frontiers in Earth Science, 2023)
Assessing the potential impacts of future urban expansion on multiple ecosystem services (ESs) is essential to contribute to the sustainability of the transnational area of Changbai Mountain (TACM). However, the potential ES losses attributed to future urban expansion have been assessed in few studies. In this study, we evaluated the potential ES losses attributable to urban expansion in the TACM for the period from 2015 to 2050. To achieve this objective, multiple ESs, namely, food production (FP), carbon storage (CS), water retention (WR), and air purification (AP), were initially quantified based on 1992 data, and we subsequently simulated urban expansion from 2015 to 2050 by coupling Shared Socioeconomic Pathways (SSPs) with the zoned Land Use Scenario Dynamics-urban (LUSD-urban) model. Finally, the potential impacts on ESs originated from future urban expansion were evaluated at multiple scales. The results indicated that during the period from 2015 to 2050, the extent of urban land will grow by between 157.59 and 517.77 km2, resulting in FP, CS, WR, and AP losses of 193.76–684.39 thousand t, 1.47–5.24 million t, 8.74–30.00 million t, and 0.34–1.18 thousand t, respectively. The portion of the transnational zone located in the Republic of Korea will experience the most severe future losses in ESs, with losses of FP, CS, WR, and AP respectively 1.06–3.77-, 1.15–3.46-, 1.10–3.54-, and 1.08–3.21-fold higher than those historically recorded in this subregion. Specifically, the encroachment of cropland and woodland by new urban land will be the main reason contributing to the future declines in ESs. Furthermore, the reductions in ESs attributable to urban expansion in this subregion will have serious impacts on human well-being. It is predicted that by 2050, the loss of FP will affect approximately 9.58% to 30.00% of the population. Moreover, among the residents of this subregion, the loss of AP will contribute to an additional expenditure of 6.63–19.81 million euros on air purification measures. On the basis of these findings, we recommend that stringent relevant policies be introduced and necessary scientific measures taken to promote the sustainable development of the TACM.